LEARNING STRATEGIES OF HIGH ENGLISH PROFICIENCY STUDENTS MAJORING IN INFORMATION SYSTEMS - Angela Bayu Pertama Sari; Cindyra Galuh Wardani; Nur Amalia Solikhah (IKIP Siliwangi, 2024)
This qualitative exploratory study, utilizing the Strategy Inventory of Language Learning (SILL), examines English learning strategies among 16 high English proficiency students majoring in Information Systems. The research aims to uncover critical insights into their English language learning strategies. The results revealed two primary findings. Firstly, metacognitive strategies emerged as the most highly used strategy, with 57% of respondents using it. Metacognitive strategies, characterized by their indirect nature, enable learners to take charge of their learning process. It highlights the significance of metacognitive reflection and decision-making skills in improving English proficiency. Secondly, within each learning strategy category, three strategy actions demonstrated strikingly similar usage percentages, each at 87.5%. These strategy actions encompass focused listening during English conversations, practicing English phonetics, and creating mental associations with new words in contextual scenarios. This research underscores the significance of metacognitive strategies and practical English language learning techniques among high English proficiency students majoring in Information Systems. Future studies using a variety of research instruments can contribute positively to providing more comprehensive insights into English learning strategies.